Business intelligence applications and the web : models, systems and technologies - Zorrilla, Marta E., 1971- (Hershey PA : Business Science Reference, 2012)
'This book summarizes current research advances in BI and the Web, emphasizing research solutions, techniques, and methodologies which combine both areas in the interest of building better BI solutions'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business intelligence; World Wide Web